Determinants of corporate voluntary disclosure in a transition economy - Masum, Mofijul Hoq; Abdul Latiff, Ahmed Razman; Osman, Mohammad Noor Hisham (Business Perspectives, 2020)
Corporate voluntary disclosure becomes a burning issue in the literature of accounting throughout the last two decades. The study aims to explore the most crucial determinants that influence corporate voluntary disclosure in a transition economy. A cross-sectional study based on the pharmaceutical and chemical companies listed in the Dhaka Stock Exchange is conducted to reconnoiter the crucial determinants affecting the voluntary disclosure. Based on the agency theory, stakeholder theory, and previous literature, the determinants are selected. An unweighted disclosure index is used to measure the extent of voluntary disclosure; after that, a multivariate analysis is steered to reconnoiter the key determinants of voluntary disclosure. It is found that firm leverage and firm liquidity are the key determinants that significantly influence the corporate voluntary disclosure in a transition economy. In contrast, no significant positive association is found between voluntary disclosure and board size. In additon, it is also found that market category significantly influences voluntary disclosure with an inverse direction. This study has important implications for both the corporate people and the regulatory bodies of the transition economy. The study also helps various stakeholders of the transition economy – Bangladesh, in designing their strategies regarding the most significant determinants of voluntary disclosure.